Determinant Variables of "Gota A Gota" (Drop By Drop) Loan as A Financing Method - Jhony Alexander BARRERA LIEVANO; Sandra Miyey PARRA RAMIREZ (Communications of International Proceedings, 2024)
Micro, small, and medium-sized enterprises (MSMEs), known as Mipyme, are characterized by their significant contribution to the economy. Among the factors affecting the sustainability and longevity of such organizations is the financing they access for the development of their commercial activities. In Colombia, the illegal practice of informal lending known as "gota a gota" (drop by drop) has been prevalent, which, due to its characteristics, poses sustainability and growth challenges for MSMEs that resort to it. This research aims to determine if there is a linear relationship between variables associated with access to "gota a gota" loan. It adopts a quantitative, correlational, non-experimental, and transactional approach. A probabilistic sample of MSMEs from Bogotá city was employed, selected through simple random sampling. The main findings indicate a correlation among the analyzed variables at various levels. Additionally, two particular phenomena were identified: firstly, more than 50% of MSMEs do not have access to credit from either the formal financial sector or the informal sector, and secondly, those accessing financing from the informal system are subject to conditions imposed by lenders, including high interest rates, putting their businesses, families, and even lives at risk. The main conclusion highlights the necessity of creating financing products tailored to the needs of MSMEs by formal actors within the country's financial system.
Keywords: Commercial loan; daily pay loan; instant loan; enterprise